Associations between sensitivity to thyroid hormones and insulin resistance in euthyroid adults with obesity - Wei, Ying; Li, Xingang; Cui, Ruixiang; Liu, Jia; Wang, Guang (Frontiers in Endocrinology, 2024)
Background Impaired sensitivity to thyroid hormones (TH) was associated with metabolic syndrome. The study aimed to explore the association between central TH sensitivity indices and insulin resistance (IR) in euthyroid adults with obesity. Methods This cross-sectional study enrolled 293 euthyroid outpatients with obesity in Beijing Chao-Yang Hospital. We used the thyroid feedback quantile-based index (TFQI), thyroid stimulating hormone index (TSHI), and thyrotrophic T4 resistance index (TT4RI) to indicate central TH sensitivity. IR was assessed by homeostasis model assessment of insulin resistance (HOMA-IR), hepatic insulin resistance index (hepatic-IR), the Matsuda index, and the adipose tissue insulin resistance index (Adipo-IR). Participants were categorized according to tertiles of TH sensitivity indices. We used multiple linear regressions to explore the associations. Results There was a significant stepwise increase in HOMA-IR and Adipo-IR from the lowest to the highest tertiles of TH sensitivity indices (all P <0.05). After adjustment for age, sex, body mass index, hypertension, hyperlipidemia, and diabetes, only Adipo-IR was significantly associated with TH sensitivity indices. On average, each unit increased in TFQI, TSHI, and TT4RI was associated with 0.17 (P=0.053), 0.15 (P=0.04), and 0.005 (P=0.03) units increased in log Adipo-IR, respectively. There was no significant association between TH sensitivity indices and HOMA-IR, hepatic-IR, and the Matsuda index after adjustment for other risk factors. Conclusions Reduced central TH sensitivity was associated with increased adipose tissue insulin resistance in euthyroid adults with obesity. The results further confirmed the importance of TH sensitivity on metabolic diseases.